Molecular diversity of "Candidatus Phytoplasma mali" strains associated with apple proliferation disease in Bulgarian germplasm collection - Fránová, Jana; Koloniuk, Igor; Lenz, Ondřej; Sakalieva, Dimitriyka (Folia microbiologica, 2019)
A quarantine organism, "Candidatus Phytoplasma mali," is the causal agent of apple proliferation, one of the most important apple diseases in Europe. The genetic diversity of this pathogen in Central and Southern Europe has already been reported; however, almost no data exists from Eastern Europe. In this study, "Ca. P. mali" strains, which were identified in 14 apple trees from the Bulgarian germplasm collection, were characterized by restriction fragment length polymorphism (RFLP) and sequence analysis of four genomic loci. In total, nine distinct genetic lineages were recognized based on the combination of the following detected RFLP profiles: two profiles for the 16S-23S rDNA region (16SrX-A2, -A3), four profiles for the secY gene (one previously known: secY(X)-A, and three new: secY-C, secY-D, secY-E), three profiles for the rpl22-rps3 genes (rpX-A, rpX-B, rpX-F), and one profile for the nitroreductase- and rhodanese-like gene (AT-1). Phylogenetic analysis of the Bulgarian and other European "Ca. P. mali" strains based on 16S-23S rRNA gene sequences confirmed RFLP grouping, regardless of the phytoplasma origin. In a phylogenetic tree based on the secY data, only German strains formed separate clade from the other strains. The tree based on rp genes did not correspond to RFLP profiles. Unexpectedly, when using nitroreductase and rhodanese-like gene sequences, the Bulgarian strains clustered separately from the other European strains. Apart from the identification of different "Ca. P. mali" strains, the paper also recommends the unification of the rpX-subgroup nomenclature to avoid future confusions. Both aims of this paper provide valuable tools to understand the epidemiology of this quarantine pathogen.
Keywords: Malus; genetická variace; Bulharsko; RNA, Ribosomal, 23S; nemoci rostlin; proliferace buněk; RNA ribozomální 16S; Genes, Bacterial; sekvenční analýza DNA; Phytoplasma; Genome, Bacterial; Sequence Analysis, DNA; Bulgaria; RNA ribozomální 23S; fylogeneze; polymorfismus délky restrikčních fragmentů; DNA bakterií; bakteriální geny; genom bakteriální; Genetic Variation; Seed Bank; Plant Diseases; Cell Proliferation; DNA, Bacterial; Polymorphism, Restriction Fragment Length; semenná banka; RNA, Ribosomal, 16S; Phylogeny